Validation of a screening algorithm for hepatic fibrosis by Doppler ultrasound and elastography in a general population. (May 2023) - Renard, Anne-Sophie; Paisant, Anita; Cartier, Victoire; Calès, Paul; Goyet-Prelipcean, Mirela; Geagea, Edmond; Tasu, Jean-Pierre; Silvain, Christine; Wagner, Mathilde; Cleach, Aline Le; Vilgrain, Valérie; Castera, Laurent; et al.
Background: Early detection can prevent the initial stages of fibrosis from progressing to cirrhosis. Purpose: To evaluate an algorithm combining three echographic indicators and elastographic measurements to screen for hepatic fibrosis in an unselected population. Material and Methods: From May 2017 to June 2018, all patients with no history and no known chronic liver disease who were referred for an ultrasound (US) were prospectively included in eight hospitals. The indicators being sought were liver surface irregularity, demodulation of hepatic veins, and spleen length >110 mm. Patients presenting at least one of these underwent elastography measurements with virtual touch quantification (VTQ) or supersonic shear imaging (SSI). If elastography was positive, patients were referred to hepatologist for fibrosis evaluation. Reference standard was obtained by FibroMeter VCTE or biopsy. A FibroMeter VCTE result >0.384 indicated a "necessary referral" to a hepatologist. Results: Of the 1501 patients included, 504 (33.6%) were positive for at least one US indicator. All of them underwent US elastography, with 85 being positive. Of the patients, 58 (3.6%) had a consultation with a liver specialist: 21 had positive FibroMeter VCTE and nine had an indication of biopsy for suspicion of fibrosis. This screening algorithm made it possible to diagnose 1.6% of patients in our population with unknown fibrosis. Of the patients, 50% referred to the liver specialist were "necessary referrals." Conclusion: Our study suggests that three simple US indicators with no systematic elastographic measurement could be applied in day-to-day practice to look for hepatic fibrosis in an unsuspected population allowing relevant referrals to a hepatologist.